Helikálně chirální aromáty - Starý, Ivo; Stará, Irena G (Chemické listy, 2014)
The review deals with the chemistry of helically chiral polyaromatics represented by helicenes. Attention is paid to synthetic methods that can be used for the preparation of helicenes, heterohelicenes and helicene analogues. Of them, the Co- or Ni-catalysed [2+2+2] cycloisomerisation of aromatic triynes to form the helical scaffold, a method developed at the Institute is reviewed. After six decades of helicene chemistry, the interest in these unique aromatic compounds is gradually increasing. As the synthesis of helicenes has recently witnessed a significant progress, their applications in various branches of chemistry, physics and nanoscience can be expected.
Keywords: Stereoisomerism; vztahy mezi strukturou a aktivitou; Structure-Activity Relationship; acetylen; stereoizomerie; katalýza; polycyklické sloučeniny; Catalysis; Organic Chemistry Phenomena; heliceny; Acetylene; pojmy organické chemie; Polycyclic Compounds